(untitled) (Ameghiniana, 2021)
The New Zealand tuatara (Sphenodon) is the sole survivor sphenodontian of a once thriving group across Pangea during early Mesozoic times. Outside New Zealand, close relatives of the tuatara (sphenodontines) are known from a few Jurassic records in North America and Europe and from end-Cretaceous fragmentary remains in Patagonia, but the evolutionary relationships of most of them remain elusive. Here we describe a new sphenodontine, Tika giacchinoi gen. et sp. nov., based on well-preserved cranial and postcranial remains from upper levels of the Candeleros Formation (Cenomanian) at the Konservat-Lagerstätte of ‘La Buitrera Paleontological Area’ in northern Patagonia, Argentina. Our phylogenetic analysis recovered Tika as a close relative of the tuatara, together with Laurasian and Patagonian taxa. The new finding represents the oldest certain sphenodontine from Gondwanan continents and reinforces the idea that particular terrestrial ectothermic tetrapods attained a circumantarctic Cretaceous-Tertiary distribution. As the extant tuatara, Tika is estimated to have fed upon a variety of prey items including small vertebrates, being ecologically distinct from the large herbivorous sphenodontians already known from La Buitrera. Tika expands the known diversity of sphenodontians during the Late Cretaceous in Patagonia, indicating that, despite already declined or extinct in Laurasia, they were still taxonomic and ecologically diverse in southwestern Gondwana.